1977
DOI: 10.3758/bf03197396
|View full text |Cite
|
Sign up to set email alerts
|

The intricacy of memory span

Abstract: The effects of word frequency on memory span were explored using the "up-and-down" method. Mean spans were greatest when the sequences were of all high-frequency words (5.82), and smallest when they were of all low-frequency words (4.24). For mixed-frequency sequences, mean spans were greater when the high-frequency words were presented before the low-frequency words (5.19) than when the low-frequency words came first (4.65). The findings are discussed in terms of the primary-secondary memory distinction worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
119
2

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 18 publications
10
119
2
Order By: Relevance
“…Nairne's feature model makes a similar assertion (Nairne, 1990). At the empirical level, word frequency effects in span (Tehan & Humphreys, 1988;Watkins, 1977) could well stem from semantic features facilitating the deblurring process. Poirier and Saint-Aubin's (1995) demonstration of the facilitative effects oftaxonomic similarity on span is a more obvious example of semantic features affecting immediate recall.…”
Section: Discussionmentioning
confidence: 90%
“…Nairne's feature model makes a similar assertion (Nairne, 1990). At the empirical level, word frequency effects in span (Tehan & Humphreys, 1988;Watkins, 1977) could well stem from semantic features facilitating the deblurring process. Poirier and Saint-Aubin's (1995) demonstration of the facilitative effects oftaxonomic similarity on span is a more obvious example of semantic features affecting immediate recall.…”
Section: Discussionmentioning
confidence: 90%
“…Watkins (1977) demonstrated a difference in span for high-and low-frequency words, whereas Wright (1979) showed a corresponding difference in the time taken to read 25-item lists of high-and low-frequency words. Schweickert and Boruff (1986) and Standing et al (1980) showed that memory span for a number of different materials (e.g.…”
mentioning
confidence: 99%
“…HF words outperform LF words in pure lists (e.g. only HF or only LF, Caplan, Madan, & Bedwell, 2015;Hulme, 2003;Hulme et al, 1997;Watkins, 1977) and WM capacity appears greater for more familiar naturally occurring stimuli (Xie & Zhang, 2016.…”
Section: Natural Word Frequency and Wmmentioning
confidence: 99%
“…Performance in immediate serial recall is better when the first half of each mixed list contains HF words and the second half contains LF words, rather than the reverse; performance on both types of mixed lists is intermediate between pure HF lists and pure LF lists (e.g., HH > HL > LH > LL, where the two letters reflect word frequency within the first and the second half of the lists; see Figure 18, Miller & Roodenrys, 2012;Watkins, 1977). In addition, the word frequency effect increases with serial position in immediate serial recall (Hulme, 2003;Hulme et al, 1997).…”
Section: Pure Vs Mixed List Paradoxesmentioning
confidence: 99%
See 1 more Smart Citation